The Risks of Nation-Building through Military Aid and Intervention - Eugen Dimant; Tim Krieger; Daniel Meierrieks (Center for Economic Studies and ifo Institute (CESifo), 2022)
This chapter discusses the role of military interventionism and aid in nation-building. We argue that (1) intervention strategies of foreign actors like the United States often unfavorably interact with local institutional settings, which (2) produces undesired outcomes not only for the target country of foreign intervention but also the intervening power. In line with these main findings, we also provide insights from our own empirical work (Dimant et al., 2022) showing that U.S. military aid has not been successful in enhancing military capacity in the recipient countries of military aid, but has rather contributed to exclusion and corruption. These unfavorable effects are, in turn, likely to produce anti-American resentment.
Keywords: D74; F35; P45; 330; U.S. military aid; nation-building; interventionism; anti-American terrorism